Effect of electrolyte and flotation collector on foam films in the presence of frothers. (31st December 2022) - Pan, Yueyi; Bournival, Ghislain; Karakashev, Stoyan I.; Yang, Bingyu; Wang, Liguang; Ata, Seher
Highlights: Xanthate (PAX) enhances the adsorption of the frother on the film surfaces. PAX greatly improves the stability of films in the presence of frothers. Salt dampens the stability of films in the frother/PAX solutions. Films of higher stability rupture at a smaller thickness. Abstract: The growing complexity of mineralogy and environmental considerations requires mineral concentrators to maximise the synergistic effect of reagent mixtures and salts on flotation performance. There is thus an increasing need to study those interactions. This paper examines the stability of thin liquid films formed from frother solutions in the presence of a collector, i.e., potassium amyl xanthate (PAX) and an electrolyte (NaCl). Two different frothers were used: methyl isobutyl carbinol (MIBC) and di polypropylene glycol (DPG). The film thinning process was recorded to determine the film lifetime. The rupture thickness was calculated, and the surface potential was obtained from the films that reached an equilibrium state. The presence of 1 ppm PAX significantly improved the stability of films in certain solutions of DPG (10–2 × 10 3 ppm) and MIBC (1 × 10 2 –2 × 10 3 ppm), where the films could be stable at a very small thickness. The changes in the surface potential of films generated in DPG and DPG/PAX solutions suggested that the addition of PAX influenced the frother adsorption on the film surface and supported a molecular interaction between xanthate and frother molecules at the air–water interface. Overall, adding salt decreased the stability of films with frother/PAX. Higher salt concentrations reduced the film stability, and the films generally ruptured at a greater thickness. Specifically, in the presence of 2 M NaCl, the stability of the films formed from the frother/PAX solutions significantly declined at higher frother concentrations, probably due to the generation of microbubbles or oil droplets. The cooperative effect between the frother, PAX and NaCl was evidently seen from the film behaviour of the ternary system. The stabilities of those films were more affected by the presence of salt than PAX. Closer attention needs to be paid to the presence and concentration of salt in monitoring the flotation pulp in a plant.